ANALISIS PERSEDIAAN BAHAN BAKU PADA INDUSTRI BAWANG GORENG âMAHKOTAâ DI KOTA PALU - Sappemasse, Sappemasse; Howara, Dafina (AGROTEKBIS, 2017)
This study aims to determine the magnitude of the number of economically purchase of raw materials, the total cost of the raw materials supplies, safety stock of raw materials and when to perform re-ordering of raw materials to the industry onions Fried Onions "Mahkota" in the city of Palu. The research was conducted on Industry Fried Onions "Mahkota" located at Jl. I Gusti Ngurah Rai from March to June 2016. The respondents were taken in this study that the company leadership fully responsible and know the raw material management of Industry Fried Onions "Mahkota". The results showed that: (1). economical purchase amount of raw materials every order was 3,000 kg, with a frequency purchase 4 times per 1 year; (2). total cost of supplies based on the EOQ method from January-December 2015 average of Rp. 3,000,000/year; (3). Safety stock of raw materials onions which should be available is 33.3 kg or 2,966.7 kg/ 3 months; (4). The length of time reordering reorder point (ROP) one day in order the arrival of raw materialson time.